Control scheme of adaptive feedforward cancellation considering of Bode's integral theorem for synchronous vibration suppression in rotating machineries. (November 2021) - Yabui, Shota; Inoue, Hideyuki; Inoue, Tsuyoshi
Synchronous vibration is a major obstacle to the stable operation of rotating machineries. In previous studies, active control methods were developed to compensate for synchronous vibration using actuators, such as an active magnetic bearing or a piezo actuator. Adaptive feedforward cancellation is another well-known control method and is used to compensate for the synchronous vibration in the actual system. The control methods can compensate for the synchronous vibration; however, the amplitude of the vibration in other frequency ranges can be increased by the waterbed effect due to Bode's integral theorem. Therefore, there is a trade-off between the compensation of the synchronous vibration and the negative impact of other vibration. In this article, a novel control scheme for the adaptive feedforward cancellation is proposed to eliminate the negative impact due to the waterbed effect. The proposed method controlled the input signal of the adaptive algorithm in the adaptive feedforward cancellation and realized an ideal feedforward controller worked independently from the feedback loop. The effectiveness of this method was verified experimentally using a test rig.